Calmodulinopathy in inherited arrhythmia syndromes - Wen-Chin Tsai; Peng-Sheng Chen; Michael Rubart (Tzu Chi Medical Journal)
Calmodulin (CaM) is a ubiquitous intracellular calcium sensor that controls and regulates key cellular functions. In all vertebrates, three CaM genes located on separate chromosomes encode an identical 149 amino acid protein, implying an extraordinarily high level of evolutionary importance and suggesting that CaM mutations would be possibly fatal. Inherited arrhythmia syndromes comprise a spectrum of primary electrical disorders caused by mutations in genes encoding ion channels or associated proteins leading to various cardiac arrhythmias, unexplained syncope, and sudden cardiac death. CaM mutations have emerged as an independent entity among inherited arrhythmia syndromes, referred to as calmodulinopathies. The most common clinical presentation associated with calmodulinopathy is congenital long QT syndrome, followed by catecholaminergic polymorphic ventricular tachycardia, both of which significantly increase the possibility of repeated syncope, lethal arrhythmic events, and sudden cardiac death, especially in young individuals. Here, we aim to give an overview of biochemical and structural characteristics of CaM and progress toward updating current known CaM mutations and associated clinical phenotypes. We also review the possible mechanisms underlying calmodulinopathy, based on several key in vitro studies. We expect that further experimental studies are needed to explore the complexity of calmodulinopathy.